2017
DOI: 10.1111/jerd.12326
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milling and postmilling procedures on the surface roughness ofCAD/CAMmaterials

Abstract: All hard-milling CAD/CAM materials, that is, fully sintered, should be only hand polished. The glaze step can be suppressed resulting in time saving. However, the glaze step in soft-milling lithium disilicate is imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 23 publications
6
33
1
5
Order By: Relevance
“…[23][24][25] Some studies reported that polishing was as effective as glazing in reducing surface roughness of ground ceramics. [26][27][28][29][30][31][32][33] Similar findings were reported for monolithic and opaque zirconia. 34,35 On the other hand, other studies reported that glazing is the best procedure for obtaining surface smoothness.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…[23][24][25] Some studies reported that polishing was as effective as glazing in reducing surface roughness of ground ceramics. [26][27][28][29][30][31][32][33] Similar findings were reported for monolithic and opaque zirconia. 34,35 On the other hand, other studies reported that glazing is the best procedure for obtaining surface smoothness.…”
supporting
confidence: 60%
“…Porcelain polishing reduced surface flaws and defects and enhanced the resistance of the restoration to fracture . Some studies reported that polishing was as effective as glazing in reducing surface roughness of ground ceramics . Similar findings were reported for monolithic and opaque zirconia .…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies 19,20 reported that glaze treatment is preferred to surface polishing for LDS restorations. Based on these studies, 26,27 the effects of different glazing treatments on the optical properties and roughness of an LDS material were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%